Carers' involvement in telecare provision by local councils for older people in England: perspectives of council telecare managers and stakeholders. Issue 2 (8th February 2021) - Steils, Nicole; Woolham, John; Fisk, Malcolm; Porteus, Jeremy; Forsyth, Kirsty
Abstract: This paper explores telecare manager and other 'stakeholder' perspectives on the nature, extent and impact of family and other unpaid/informal carers' involvement in the provision of telecare equipment and services for older people. Data used in the paper are derived from a larger study on telecare provision by local councils in England. The paper aims to add to the growing evidence about carers' engagement with electronic assistive technology and telecare, and considers this in the context of typologies of professionals' engagement with carers. How carers are involved in telecare provision is examined primarily from the perspectives of senior managers responsible for telecare services who responded to an online survey and/or were interviewed in 2016 as part of a wider study. The perspectives of three unpaid carers were captured in a separate strand of the main study, which comprised more detailed case study interviews within four selected councils. Thematic and comparative analysis of both qualitative and quantitative survey data revealed the varied involvements and responsibilities that carers assumed during the telecare provision process, the barriers that they needed to overcome and their integration in local council strategies. Findings are discussed in the context of Twigg and Atkin's typology of carer support. They suggest that carers are mainly perceived as 'resources' and involvement is largely taken for granted. There are instances in which carers can be seen as 'co-workers': this is mainly around responding to alerts generated by the telecare user or by monitored devices, but only in those councils that fund response services. Though some participants felt that telecare devices could replace or 'supersede' hands-on care that involved routine monitoring of health and wellbeing, it was also acknowledged that its use might also place new responsibilities on carers. Furthermore, the study found that meeting carers' own rights as 'co-clients' was little acknowledged.